Impacts of anthropogenic and boreal fire emissions in the central North Atlantic lower free troposphere: summertime observations at the PICO-NARE observatory. - Val Martin, Maria (2013)
ICARTT 2004 Data Workshop. Durham, New Hampshire, August 9-12, 2005.